Speech by the Honourable Chief Minister, Penang, at the State Government Dinner to ASEAN Journalists and the National Union of journalists of Malaysia Officials to be held at the Wisma Persekutuan on Friday, 11th June 1976 at 8.00 p.m. - Lim, Chong Eu (1976)
It gives me great pleasure to welcome to Penang the Journalists attending the First Annual Conference of the Confederation of ASEAN Journalists in Kuala Lumpur which was opened by the Honourable Prime Minister of Malaysia,Y.A.B. Datuk Hussein Onn recently.